Field-Testing Astronaut Assistance Robots in Australian Outback [From the Field] - Mann, G.; Small, N.; Lee, K.; Clarke, J.; Sheh, Raymond (Institute of Electrical and Electronics Engineers, 2015)
Reports on the field testing of robots technology. The trouble with field-testing robots is that we are taking complex machines out of the laboratory and into the dirt: natural, unstructured environments that cannot be easily characterized or measured. There they could be doing imperfectly characterized tasks. We expect robots to be behaviorally flexible so describing a typical task will generally underspecify actual usage. The machine design, task, and environment are not orthogonal factors either, since they might interact in complicated ways. As if all this was not enough, most field robots are still teleoperated, which adds the attendant problems of evaluating the human controller and interface. Published work in this area tends to focus on demonstrating the robot's fitness for purpose based on specific requirements, often according to the contingencies of practical funding. Too often that commits the work to studies of performance on tasks that are not necessarily well understood, or even particularly well described, and to measurements within environments that cannot be duplicated.